Non-destructive assessment based on impedance properties to determine postharvest quality of rockmelon - Jumadi, Mohd Shahrul Azwan; Jamaludin, Diana (Penerbit MARDI, 2018)
The objective of this study was to evaluate the feasibility of impedance properties to determine rockmelon fruit postharvest quality parameters (storage period, moisture content and weight-loss) using an impedance analyser board (AD5933) with a pair of ECG electrodes at frequency range of 100 Hz to 100 kHz. The study shows that as the storage period is prolonged, the impedance value, weight, and moisture content of rockmelon are decreased. The best frequency range from 400 Hz to 600 Hz was used to differentiate all the samples based on their impedance value and storage period. The best prediction based on impedance value by linear regression model for storage period can be determine at frequency of 540 Hz with r² = 0.93 and the root mean square error (RMSE) = 2.48, while for moisture content is at 400 Hz frequency with r² = 0.81 and RMSE = 1.53. Prediction of soluble solid content with impedance value is by a polynomial equation at 580 Hz with r² =0.95. From all these results, it indicates that electrical impedance properties have a good potential to develop a sensing system that can measure the rockmelon storage period, moisture content, weight and SSC level without destructing the fruit.